The Big Five Personality Traits in Relation with Job Satisfaction among UNRWA Teachers in the Educational Area of Irbid - Bukaiei, Nafez (Jordan Journal of Educational Sciences, 2015)
This study aimed at recognizing the relation between the big five personality traits and the job satisfaction among UNRWA schools in the educational area of Irbid. The study also aimed at identifying the most common personality trait and the degree of job satisfaction according to the variables of sex, teaching experience, qualification, and the grades that are taught by UNRWA teachers. To achieve the aims of this study, the gauge of the big five personality traits of John, Donahue & Kentle (1991) was applied. In addition, the researcher molded the gauge of job satisfaction for UNRWA teachers to achieve the aims of this study. The sample of this study consisted of (187) male and female teachers that were selected on the basis of (random cluster). The results demonstrated that the commonest personality trait is agreeableness and the least common one is neuroticism. The results also showed that there are differences in the traits of extraversion and consciousness attributed to the variable of sex in favor of females; there are also differences in the trait of extraversion according to the variable of teaching experience in favor of those getting the highest experience. The results also showed that there are differences in the trait of agreeableness attributed to the variable of the grades in favor of the first three grades. The results also demonstrated that there are no differences in the level of job satisfaction in terms of all the variables of this study except a difference in job satisfaction attributed to the variable of sex in favor of females. Finally, the results exhibited that there is a statistically positive relationship between the traits of extraversion, agreeableness, consciousness and job satisfaction whereas there is a negative relationship between neuroticism and job satisfaction.